Pengolahan Gas Buang Hasil Pembakaran Campuran Refuse Derived Fuel dan Serbuk Gergaji dengan Spray Tower Scrubber - Ilmi Ilmi; Junjungan Simamora; Suherman Suherman; Zufri Hasrudy Siregar (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
The growing volume of waste has encouraged the use of fuel derived from waste as an alternative energy source. However, its combustion releases flue gas containing harmful pollutants. This study assesses the effectiveness of a spray tower in reducing the opacity and temperature of flue gas generated from the combustion of a mixture of waste-based fuel and sawdust. Experiments used three fuel masses and three system setups: no sprayer, two sprayers, and four sprayers. Results showed that the spray tower reduced opacity from 33 per cent to about 15 per cent with two sprayers and 11.2 per cent with four sprayers. Gas temperature decreased from 65 degrees Celsius to 39 degrees and 35 degrees Celsius. A higher number of sprayers led to greater pollutant reduction. This technology shows promise as an environmentally friendly method for controlling emissions.